Analisis Daya Dukung dan Penurunan Fondasi Tiang dengan Berbagai Metode - Meiprastyo, Xbal; Rono IS Rono Hadinagoro; Prima Sukma Yuana; Ragil Rajvikhal (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2024)
A bridge is the main infrastructure that connects two parts that are cut off due to an obstacle that cannot be built conventionally. To expedite and facilitate land transportation, bridges are needed to connect one region to the next. The foundation is one part of building construction which functions to place the building and transmit the load distributed from the upper structure to the foundation soil which is strong enough to support it without differential settlement occurring in the structural system. At this project location, a type of suspension bridge was chosen using a Strauss pile foundation. The aim of this research is to analyze the bearing capacity and settlement of foundations based on Standard Penetration Test (SPT) data, laboratory tests and sondir/Cone Penetration Test (CPT). In this study, the depth and diameter used are the same, the only difference is the method used. Based on the analysis results, the bearing capacity value using N-SPT data was 2021.72 kN, while the permit carrying capacity value using Laboratory and Sondir data was 1108.98 kN and 804.71 kN respectively.